(3eNJUQ GdZhGeV hGdeHgeGJ (B( (3aj GdCSeGA GdhGbYI aj GdCMGOjK (B)s - (3EHQGgje Hf eMeO Hf Ndjd GdnqWnQGoHodSj Ke GdMdHj, CHh GdhaGA, HQgGf GdOjf, pSrHW GHf GdnYnLej , J (B841 (3g` s; (3GHf HTchGd , Nda Hf YHO Gdedc Hf eSYhO Hf HTchGd GdNRQLj GdCfUGQj, CHhGdbGSe,J (B578 (3g` s
(3ChdgG (B:s
(3Chdg HYO GdHSedI (B:(3GdNHQ GdChd Yf WdMI Hf YHO Gddg bGd s
(3BNQgG (B:s
(3aQZJ efg jhe GdCMO NGeS YTQ TgQ QeVGf SfI (B771 (3Ydbg EHQGgje SHW GHf GdYLei , WdHI ddaGFOI CMSf Gddg NGJeJg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B137 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs